New edition of the PN-B-02877-4 standard, gravity smoke exhaust system. What has changed? - Kubicki, Grzegorz (Instal, 2025)
After many years of waiting, a new version of the standard PN-B-02877-4:2025-07 has been published on the PKN website. The revised standard, based on the structure of the withdrawn document, has been significantly modified and expanded with new content. This article discusses the key changes in the standard, including its scope, the deeply modified and more detailed principles for selecting components for smoke ventilation systems in PM buildings and stairwells in multi-story buildings. The article also draws attention to entirely new provisions concerning, among other things, the principles for determining the size of air inlet openings for compensatory airflow, wall-mounted devices for smoke removal, heating, control, activation, testing, and oversight of the system. The article also includes the author’s subjective assessment of the new version of the standard and a justification for the recommendation to apply it.
Keywords: smoke extraction; natural smoke and heat exhaust ventilators; fire safety; fire ventilation